X-Ray Polarization of BL Lacertae in Outburst - Peirson Abel L.; Negro Michela; Liodakis Ioannis; Middei Riccardo; Kim Dawoon E.; Marscher Alan P.; Marshall Herman L.; Pacciani Luigi; Romani Roger W.; Wu Kinwah; Di Marco Alessandro; Di Lalla Niccoló; et al. (Institute of Physics Publishing, 2025)
We report the first >99% confidence detection of X-ray polarization in BL Lacertae. During a recent X-ray/γ-ray outburst, a 287 ks observation (2022 November 27–30) was taken using the Imaging X-ray Polarimetry Explorer (IXPE), together with contemporaneous multiwavelength observations from the Neil Gehrels Swift observatory and XMM-Newton in soft X-rays (0.3–10 keV), NuSTAR in hard X-rays (3–70 keV), and optical polarization from the Calar Alto and Perkins Telescope observatories. Our contemporaneous X-ray data suggest that the IXPE energy band is at the crossover between the low- and high-frequency blazar emission humps. The source displays significant variability during the observation, and we measure polarization in three separate time bins. Contemporaneous X-ray spectra allow us to determine the relative contribution from each emission hump. We find >99% confidence X-ray polarization π2-4KeV = 21.7-7.9+5.6 %  and electric vector polarization angle ψ2–4keV = −28˚̣7 ± 8˚̣7 in the time bin with highest estimated synchrotron flux contribution. We discuss possible implications of our observations, including previous IXPE BL Lacertae pointings, tentatively concluding that synchrotron self-Compton emission dominates over hadronic emission processes during the observed epochs.